Morfometrijska analiza varijabilnosti svojstava lista hrasta lužnjaka (Quercus robur L.) na području sjeverne Bosne - Bašić, Neđad; Kapić, Jasminko; Ballian, Dalibor (2007)
The paper deals with among- and within-population variability for nine leaf morphological traits (lamina length, petiole length, length of lamina from the base to the widest point of leaf, width of lamina from the tip of the widest lobe to the midrib on the left side of the leaf, sinus width¸ width of lamina, sinus of lamina base, number of lobes on the right side of the leaf, lamina shape f/a-LL-index) of common oak tree populations. The analysed material encompassed four populations from northern part of Bosnia. Morphometric analysis showed that the most variable traits were the sinus of lamina base, petiole length and sinus width. The other traits analysed had significantly lower values of variation coefficients. Analysis of variance (ANOVA) revealed significant differences between and among populations. Using the Fisher multiple tests (LSD), the highest number of differences were observed in Novi [eher population. This accession had the highest number of leaf traits differing from other populations. Following characteristics displayed significant differences among all populations: lamina length, length of lamina from the base to the widest point of the leaf, width of lamina from the tip of the widest lobe to midrib on the left side of the leaf, width of lamina. Sinus width did not differ between the populations
Bibliografija: 15 jed
Summary
Keywords: Hrast lužnjak -- List -- Varijabilnost